PENGARUH NILAI BERITA HOUSE JOURNAL SINAMAR TERHADAP PEMBENTUKAN CITRA POSITIF PEMERINTAH DIMATA MASYARAKAT KABUPATEN LIMAPULUH KOTA SUMATERA BARAT - Wahyudi, Indra; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Judging from the development history, communicate to influence the outlook and behavior of people has started since time immemorial. This is evident in the slogan Vox Populi, Vox dei (the voice of the people is the voice of God). In theory S-O-R communication is an action-reaction process. This means that this theory assumes that the words of verbal, non-verbal cues, certain symbols will stimulate others to respond in a certain way. Pattern S-O-R can take place in a positive or negative; for example if the person will be rewarded smile smile is a positive reaction, but if the smiling exhaust face then rewarded with a negative reaction. The purpose of this study is to determine the effect of News Values House journal Sinamar Positive Image Formation Against Government Public Eyes Limapuluh Kota.The method used in this research is a quantitative method of explanation. Data collection techniques in this study using a questionnaire. The total sample for this study of 166 respondents. Sampling using accidental sampling technique. To find out how much influence these two variables, the researchers used a simple linear regression analysis. For the processing of questionnaire data, were performed using the Statistical Product And Service Solution (SPSS) Windows version 17.Results of research on the effect of the news value house journal Sinamar to the formation of positive image in the eyes of the public district government limapuluh kota regression coefficient values obtained in this study is Y = 0.409 + 0.879 X 0.000 with a significance level of less than Î± = 0.05. This means that there is influence between newsworthy house journal Sinamar to the formation of a positive image of the government amounted to 76.3% and is categorized as a strong influence. These percentages show that the government has formed a positive image in the eyes of the public. Thus H0 is rejected and Ha accepted.Keywords: Government, House Journal, Positive Image